Successful treatment of a 67-year-old woman with urethral adenocarcinoma with the use of external beam radiotherapy and image guided adaptive interstitial brachytherapy - Mujkanovic, Jasmin; Tanderup, Kari; Agerbæk, Mads; Bisgaard, Ulla; Høyer, Søren; Lindegaard, Jacob Christian; Fokdal, Lars (Journal of Contemporary Brachytherapy, 2016)
Primary urethral cancer (PUC) is a very rare disease. This case report illustrates a successful treatment approach of a 67-year-old woman with a urethral adenocarcinoma selected for an organ preserving treatment with external beam radiotherapy (EBRT) and interstitial brachytherapy (BT) boost, using the GEC-ESTRO target concept originally designed for locally advanced cervical cancer (LACC). Treatment included EBRT with 45 Gy in 25 fractions followed by image guided adaptive interstitial BT (IGABT) with a pulsed-dose-rate (PDR) BT boost with 30 Gy in 50 hourly pulses. The D 90 for CTV HR was 79.1 Gy in EQD23. At 24 months follow-up, the patient was recurrence free and without treatment related side effects.